Social Empowerment of Social Entrepreneurship - Waligóra, Anna (Studia Oeconomica Posnaniensia, 2015)
The issue of social entrepreneurship in Poland is discussed from many points of view. In the context of the functioning and development of this social phenomenon the position of both theoreticians (creator definitions, scientific studies and research), the creators of laws and established their advisory bodies, bodies that encourage social entrepreneurship from public funds, including trans-national (m.al. EU ) and representatives of the business areas of cooperation for social entrepreneurship entities . The purpose of this article is to present the different points of view and references for the development of social entrepreneurship in Poland, as well as the evaluation of the actions undertaken for the development of social entrepreneurship in Poland.